Stability of a PKCI-1-related mRNA is controlled by the splicing factor ASF/SF2: a novel function for SR proteins - Lemaire, Raphael (Cold Spring Harbor Laboratory Press, 2002)
Pre-mRNA splicing is a widely used regulatory mechanism for controlling gene expression, and a family of conserved proteins, SR proteins, participate in both constitutive and alternative splicing. Here we describe a novel function for the SR protein ASF/SF2. We used an embryonic chicken cDNA library to screen for differential mRNA expression in the chicken B-cell line DT40-ASF, expressing or not expressing ASF/SF2. Remarkably, out of 3 × 10(6) clones screened, only one, isolated several times independently, showed ASF/SF2-related differential expression. The isolated cDNA, referred to here as PKCI-r (for PKCI-related), is closely related to the protein kinase C interacting protein (PKCI-1) gene. Transcript levels were increased ∼sixfold in ASF/SF2-depleted cells compared with cells expressing ASF/SF2, indicating a negative role for the SR protein. Strikingly, inhibition of ASF/SF2 expression had no significant effect on PKCI-r splicing, or transcription, but markedly increased the half-life of PKCI-r mRNA (6.6-fold). Similarly, increased mRNA stability was also observed upon expression of exogenous PKCI-r mRNA in cells depleted of ASF/SF2. ASF/SF2 bound to a discrete region containing a purine-rich sequence in the 3′ UTR of the PKCI-r transcript, and deletion of this region eliminated ASF/SF2-mediated regulation of transcript stability. Together these data indicate a novel, direct effect of ASF/SF2 on PKCI-r mRNA stability. Therefore, ASF/SF2, and perhaps other SR proteins, affects gene expression in vertebrate cells through regulation of mRNA stability as well as splicing.